The inclusion of habits in the stage model of self-regulated behavior change: an investigation of life events and red meat consumption in the UK - Colin Whittle; Nick Nash; Paul Haggar; Lorraine Whitmarsh (Frontiers in Psychology)
A shift to a diet with low or no red meat is considered necessary to end the environmental and health impacts caused by the current overconsumption of red meat. The self-regulated behavior change stage model (SSBC) proposes that people who intend to change their behavior progress through a series of discrete cognitive stages until, ultimately, they engage in the new behavior. However, what the consequences of habitual behaviors are for the initiation and progression through the stages of change have not yet been fully elucidated or investigated. We hypothesized that habitual behaviors that are antagonistic toward an alternative behavior will inhibit the initiation and progression through the stages of change. Furthermore, in line with the habit discontinuity hypothesis, we hypothesized that the experience of life events would counteract antagonistic habits and be positively associated with stages of change. Using a cross-sectional survey of people who consume red meat in the UK, our findings support the SSBC concept of stage-specific cognitive processes with goal intention and goal feasibility varying in importance depending on stage membership. However, personal norms were equally important for stage membership regardless of stage. Our hypotheses for antagonistic habits and life events were also partially supported; the antagonistic habit was not negatively associated with goal intention to change, but it was associated with a reduced likelihood of being in the final stage of change (i.e., of engaging in reduction). Experience of a life event was positively associated with goal intention to change, but it was negatively associated with being in a later stage of change. Overall, our findings provide novel theoretical insights into the role of habits and habit disruption in a stage model of behavior change. They also yield applied implications for understanding how to achieve a reduction in the over-consumption of red meat (or other, habitual, high greenhouse gas emitting behaviors) by supporting the importance of stage-tailored behavior change interventions and suggesting the potential to combine such stage-tailored intervention strategies with the strategy of targeting interventions to when existing habits are weakened due to context disruption.